Efektifitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Di Kabupaten Klaten Pada Bencana Letusan Gunung Berapi Dengan Menggunakan Strategi Numbered Head Together Terhadap Hasil Belajar Siswa Di SMA Negeri 1 Klaten - Astuti, Anggun Puji; , Dra.Siti Taurat Aly, M.Pd (2016)
This research to knowing: (1) To knowing disaster learning book in Klaten is effective to learn about mountain erupted disaster in SMA Negeri 1 Klaten. (2) To knowing how to used numbered head together strategy could increase the result of the study. (3) To knowing relation between disaster learning book in Klaten with numbered head together strategy. The population to used on this research is students XI IPS 1 and XI IPA 7. Sample on this research is students XI IPS 1 and XI XI IPA 7. Sample to used on this research is 25 students every class, consisting of XI IPS 1 as experiment class and XI IPA 7 as class control. Data collection using test, observasion, and documentation. Data analysis using Uji wilcoxon. The conclusion of this research is class with learning numbered heads together strategycan increase than class with conventional metode, learn using numbered heads together more effective than using conventional metode on this research. Key words: Effective, Numbered heads together, Learning result.